WAYS TO IMPROVE DIVIDEND POLICY IN JOINT STOCK COMPANIES - Shamsitdinova daughter of Khanzoda Mardonbek (Scholars Digest Publishing, 2023)
In this article, the scientific-theoretical aspects of the dividend policy in joint-stock companies are studied, and the current dividend policy is analyzed.
Keywords: joint stock company, dividend policy, securities, capital, financial instruments, tax, retained earnings.